'Blind alley' to 'steppingstone'? Insecure transitions and policy responses in the downturns of the 1930s and post 2008 in the UK. (21st April 2023) - Cooper, Matthew
ABSTRACT: Even before the crisis of 2008, the growing insecurity of young people's transitions from school into work had been of concern to many observers in the UK. During the crisis itself, young people were disproportionately unemployed and concentrated in insecure employment sectors. Policy makers refrained from any labour market intervention insisting that the flexible nature of this work prevented higher unemployment. In unemployment, benefits entitlements were reduced and became subject to greater conditionality to counter a perceived crisis of social dependency. These changes have often been discussed in terms of the rise of neo-liberalism and the breakdown of post-war labour market securities. This article takes a complementary but different comparison with the 1930s, when similar liberal policy orthodoxies dominated. The evidence assembled shows significant continuities and contrasts in how youth unemployment was interpreted and responded to in the social security system and in wider labour market policies. In doing so, it illustrates the distinctive features of contemporary neo-liberalism and contributes to debates on youth unemployment, benefits and insecure work.